Microplastic Content in Blood Cockles (Anadara granosa) from the Coastal Waters of Tanah Merah Meranti Islands, Riau - Nirana Firda Caesaria Wulandari; Zulkifli Zulkifli; Bintal Amin (Jurnal Natur Indonesia, 2024)
This research was conducted in December 2023 to determine the type and content of microplastics in blood cockles (Anadara granosa) by taking samples from the coastal waters of Tanah Merah Beach, Meranti Islands. The sampling location was based on the purposive sampling method divided into residential areas, fishing ports, and mangrove areas. Blood cockle samples from the three locations were selected for only large sizes (2.5-3.7cm). The water quality parameters at the sampling location were measured for temperature, salinity, and pH, indicating that the coastal waters of Tanah Merah Beach are still natural habitats for blood cockles. Three types of microplastics were found in blood cockles, namely fiber, film, and fragments, with an average abundance of 56.33 particles/ind (p>0.05). Further research is needed regarding size differences and relationships with environmental parameters